Decentralization under time of crisis - Galilea Ocón, Sergio (Estado, Gobierno y Gestión Pública, 2021)
The process of decentralization in Chile is going through decisive hours. It is facing the election of the regional governors, the unprecedented constitutional scenario, and the pandemic and its complex socio-economic effects.This article gives vital information of this effect. It analyzes the key reform of 1991, and the creation of the regional governments and the municipal elections of 1992 which is defined as a milestone event of the decentralization process. It also goes deep into the shadows and lights of 1994–2018, emphasizing the weaknesses of the territorial planning, the productive development, and the deficiencies of its own resources. Furthermore, it acknowledges the overall contribution of the 2014 Presidential Commission, which embraces a set of proposals of actions to strengthen this decentralization with the support and participation of the elected regional governors and majors, and with the powers given to the local government before the presidential delegate. Lastly, it shows aspects of the role of the sub-national governments towards the complex post pandemic reality.